2022
DOI: 10.1200/jco.22.00303
|View full text |Cite
|
Sign up to set email alerts
|

Cascade Testing for Hereditary Cancer Syndromes: Should We Move Toward Direct Relative Contact? A Systematic Review and Meta-Analysis

Abstract: PURPOSE Evidence-based guidelines recommend cascade genetic counseling and testing for hereditary cancer syndromes, providing relatives the opportunity for early detection and prevention of cancer. The current standard is for patients to contact and encourage relatives (patient-mediated contact) to undergo counseling and testing. Direct relative contact by the medical team or testing laboratory has shown promise but is complicated by privacy laws and lack of infrastructure. We sought to compare outcomes associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 132 publications
0
38
0
Order By: Relevance
“…[32][33][34][35] Interestingly, although several prior studies have demonstrated that females are more likely to complete cascade testing than males, we found no difference in rates of testing by sex in our cohort In summary, our long-term follow-up study demonstrates that clinician-facilitated cascade testing can result in the successful completion of genetic testing and utilization of genetically targeted primary disease prevention through screening and risk-reducing surgery with a positive patient-reported experience. These results, supported by a recent meta-analysis, 16 suggest that health care systems should consider supporting clinician-facilitated direct contact cascade testing programs, and this is to be confirmed by larger randomized controlled trials. Notably, 67% of relatives did not complete all of the NCCN-recommended cancer screening interventions, and this suggests that future strategies to promote care for families with hereditary cancer syndromes must focus not just on access to genetic testing but also on supporting engagement with the medical system after the identification of a germline pathogenic variant.…”
Section: Sexmentioning
confidence: 63%
See 2 more Smart Citations
“…[32][33][34][35] Interestingly, although several prior studies have demonstrated that females are more likely to complete cascade testing than males, we found no difference in rates of testing by sex in our cohort In summary, our long-term follow-up study demonstrates that clinician-facilitated cascade testing can result in the successful completion of genetic testing and utilization of genetically targeted primary disease prevention through screening and risk-reducing surgery with a positive patient-reported experience. These results, supported by a recent meta-analysis, 16 suggest that health care systems should consider supporting clinician-facilitated direct contact cascade testing programs, and this is to be confirmed by larger randomized controlled trials. Notably, 67% of relatives did not complete all of the NCCN-recommended cancer screening interventions, and this suggests that future strategies to promote care for families with hereditary cancer syndromes must focus not just on access to genetic testing but also on supporting engagement with the medical system after the identification of a germline pathogenic variant.…”
Section: Sexmentioning
confidence: 63%
“…The clinician‐facilitated strategy yielded promising results and achieved cancer genetic testing for 58% of total identified relatives and for 70% of relatives who were able to be reached by the research team. These results have been confirmed by a systematic review and meta‐analysis, which demonstrated cascade testing completion for 36% of relatives with patient‐mediated relative contact versus 63% of relatives when relatives are directly contacted by the medical team or testing laboratory 16 . Although this increased utilization of genetic testing is exciting, it is only clinically meaningful if action is taken in response to positive genetic testing results.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, male relatives show higher reluctance towards cascade testing than their female counterparts. [56][57][58][59] This lack of cascade testing is a concern in view of the missing opportunity to detect and prevent hereditary cancers.…”
Section: Educational Pointsmentioning
confidence: 99%
“…In most countries, the current standard approach for risk disclosure is to rely on the proband to pass on information to relatives, so called family-mediated risk disclosure. Recently, the rst meta-analysis showed that 35% [95% CI, 24 to 48] of ARRs underwent genetic counselling with family-mediated risk disclosure (2). With healthcare-assisted risk disclosure using direct contact with ARRs the uptake almost doubled to 63% [95% CI, 49 to 75].…”
Section: Introductionmentioning
confidence: 99%